Peran Pendidikan dalam Transformasi Nilai Budaya Lokal Di Era Millenial - Fauzi Fauzi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2018)
Abstract: This study is motivated by a rapid phenomenon and the enormity of life changes in the globalization era with the advancement of information and communication technology. This information age became the forerunner to the birth of the era and millennial generation; a generation that makes information and devices as a part which always attached to their lives. This study aims to describe the reality of human life in the global era with all its achievements in the form of openness and ease of interaction and communication as well as various facilities. In addition, this study is also directed at critically analyzing the problems and impacts of the advancement of the information age for humans in the form of the loss of a distinctive identity as a human in his dialectics with his social and cultural system. With the critical phenomenology approach, it is illustrated that this information era leads to the age of uniformity of systems and value of human life with the spirit of a single universal culture. This context poses a serious threat to the loss and scrape of wisdom values ​​over the value of locality. The value of local culture which is the driving force and controlling the crisis of human existence must be carried out transformation efforts towards a new direction in accordance with the spirit of locality and globality (glocalization). Efforts to transform the value of local culture in this global context require the transformative role of the world of education in its various aspects. Transforming local cultural values ​​to students can be done with the paradigm of transformative epistemology. Keywords: pendidikan, transformasi, nilai, budaya lokal, globalisasi, lokalitas, era